Gender and Public Participation in Afghanistan Aid, Transparency and Accountability - Najimi, Bashirullah (Springer International Publishing, 2018)
This book discusses the role of gender and participation within the context of budgeting and planning. Gender and participation are two very closely interconnected issues in these processes, and the author explores how these could better promote accountability and transparency. Through chapters on topics such as access to information and mechanisms for public engagement, gender responsive budgeting, and the role of women in combating corruption, the book includes examples of good practices in gender and participation from the international perspective and to what extent they could be applied in Afghanistan. Working in aid-dependent developing countries with a high level of gender inequality and corruption requires additional knowledge of issues in gender, public participation, accountability, and transparency-regardless of whether working in the public sector or in a non-governmental organization (NGO). Bashirullah Najimi is an expert of International Development who has worked extensively on public sector budgets, foreign aid management and analysis, particularly in Asia. He has worked with the International Budget Partnership, the Afghan Parliament, the Government of Dubai, and with the United Nations Development program. .